Kebijakan Luar Negeri Indonesia Terhadap Perjanjian (NPT) - Tigris Asyur Sipahutar (Dinamika Politik, 2012)
This study is the study of Indonesia's foreign policy. The focus discusses the foreign policy of Indonesia to the Nuclear Nonproliferation Treaty. The findings of this study include Indonesia supports the Nuclear Nonproliferation Treaty and its implications for the resolution can be maintained or improved position of Indonesia in the international countries. The method used is descriptive-qualitative method that is intended to describe an event in more detail.Keywords: Foreign Policy, Foreign Policy, International Treaties.